2018
DOI: 10.1108/ijcma-09-2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

How does emotional conflict affect innovation behavior?

Abstract: Purpose This study aims to offer insights regarding the impact of emotional conflict on innovation behavior. This study also explores the boundary conditions by examining the moderating effects of leader-member exchange (LMX) and team-member exchange (TMX) on the relationship between emotional conflict and innovation behavior. Design/methodology/approach This study used a questionnaire survey to collect data in China. Hypotheses were tested using hierarchical regression analysis. To test for inverted U-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…They are related to flexibility in problem-solving (Brief and Weiss, 2002), increase in creativity (Dolan and Metcalfe, 2012), engagement with behaviour (Salas-Vallina et al , 2020) and readiness to be innovative (Gomes et al , 2015), productivity improvement (Oswald et al , 2015) and willingness to creative problem solving (Bellou, 2010; Koveshnikov et al , 2014). On the other hand, negative emotions have a negative effect on innovative behaviour (Montani et al , 2016; Wu et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They are related to flexibility in problem-solving (Brief and Weiss, 2002), increase in creativity (Dolan and Metcalfe, 2012), engagement with behaviour (Salas-Vallina et al , 2020) and readiness to be innovative (Gomes et al , 2015), productivity improvement (Oswald et al , 2015) and willingness to creative problem solving (Bellou, 2010; Koveshnikov et al , 2014). On the other hand, negative emotions have a negative effect on innovative behaviour (Montani et al , 2016; Wu et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research on the joint effect of personality traits and TMX is still scarce. For instance, Wu et al (2018) demonstrated that high-quality TMX moderate the positive influences of low degrees of emotional conflict (related with emotional stability) on innovative behavior, while undermining the adverse consequences of higher levels of emotional conflict on it. Social exchanges among individuals are critical to individual performance, as they provide a wide range of performance-related understanding, as well as social and emotional support (Chung, 2020).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Previous research has shown that TMX predicts workplace outcomes such as individual performance, job satisfaction, and organizational commitment [25][26][27]. In this vein, TMX has often been introduced as a moderator in explaining the relationship between organizational antecedents and outcomes [14,[28][29][30]. The present study contributes to the literature on organizational research by theorizing and empirically verifying a mechanism that explains sub-components of PG fit linked to CI under the boundary conditions of TMX.…”
Section: Introductionmentioning
confidence: 69%
“…According to trait activation theory, we propose that TMX presents a reinforcing social environment in which individuals are hesitant to exert effort to question the organization's status quo. Since its first introduction to the literature [34], trait activation theory has been widely applied and discussed to explain work autonomy, situation strength, and trait-situation interactions in the workplace [30]. Tett and Guterman (2000) proposed an interactionist principle of trait activation, emphasizing situation-trait relevance [34].…”
Section: The Moderating Role Of Tmxmentioning
confidence: 99%